The Effect of Final Sanctions to Increase MSME Taxpayer Compliance in The City of Jambi - Edy Arisondha (Journal of Applied Business, Taxation and Economics Research, 2022)
This study aims to determine the effect of fines on the level of compliance of MSME taxpayers with a case study for the city of Jambi. Data was obtained by distributing questionnaires containing questions related to the variables studied, only 90 respondents were sampled from all MSME actors in Jambi. The data is then analyzed using a simple regression method, from the results of the analysis it is known that the significance value of fines is 0.044 less than 0.05, which means that fines can affect the level of compliance of MSME taxpayers in the city of Jambi. This research is still limited by using only the variable of penalties for measuring the level of taxpayer compliance, so it is recommended for further research to examine other variables that can affect the level of taxpayer compliance.